Preparation method of ultrasonic / magnetic field regulated flexible magnetoelectric composite film

CN122894565APending Publication Date: 2026-10-13UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611327693.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]本发明的目的在于针对现有磁电复合材料中磁性纳米颗粒随机分散、界面耦合效率低以及磁-力-电能量转换性能不足等问题,提供一种超声/磁场调控的柔性磁电复合薄膜制备方法

Benefits of technology

[0019](1)实现不同构型磁电薄膜的定向制备:本发明通过引入超声场或偏置磁场,可在制备过程中原位调控CFO纳米颗粒在薄膜中的空间分布,分别获得0-3型和2-2型两种不同构型的磁电复合薄膜,实现了薄膜微观结构的可控制备。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122894565A_ABST
    Figure CN122894565A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of biological medical devices, and particularly relates to a preparation method of a flexible magneto-electric composite film regulated by an ultrasonic field and a magnetic field. A gamma-glycine / polyvinyl alcohol (gamma-Gly / PVA) with piezoelectric performance is used as a substrate, cobalt ferrite (CFO) nanoparticles are introduced, a CFO / gamma-Gly / PVA composite film is prepared through a solution casting method, and an ultrasonic field or a bias magnetic field is introduced during the film solidification process to realize the regulation of the spatial structure of the CFO nanoparticles. The ultrasonic field promotes the uniform dispersion of the CFO nanoparticles, forming a 0-3 type magneto-electric composite structure; the bias magnetic field induces the directional distribution of the CFO nanoparticles along the upper and lower interfaces of the film, constructing a 2-2 type heterostructure, thereby optimizing the stress transmission path between the magnetostrictive phase and the piezoelectric phase, and enhancing the magnetic-force-electric coupling effect. The preparation process of the application is simple, the structure is controllable, and the application provides an effective strategy for the structural design of magneto-electric composite materials, and has a good application prospect in the fields of battery-implant-free bioelectronic devices, magneto-electric stimulation and physiological signal sensing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical device technology, specifically relating to a method for preparing a flexible magnetoelectric composite thin film regulated by ultrasound / magnetic field. Background Technology

[0002] The development of battery-free bio-implantable devices is limited by the need for efficient and stable power supply methods, while existing self-powered and wireless transmission technologies still have certain limitations. Magnetoelectric composite materials can achieve energy conversion and signal response through magneto-electric coupling, providing a potential solution for implantable bioelectronic devices. However, their performance is significantly affected by the interfacial coupling and microstructure of the magnetostrictive and piezoelectric phases. Therefore, developing efficient and controllable structural modulation strategies is crucial for improving magnetoelectric performance.

[0003] Currently, magnetoelectric composite materials mainly fall into two categories: layered heterostructures, which are formed by laminating inorganic magnetostrictive materials and inorganic piezoelectric materials through epoxy resin bonding or high-temperature diffusion bonding, offer high magnetoelectric conversion efficiency but suffer from inherent brittleness, difficult machining, and significant influence of interfacial bonding on device performance. To overcome the inherent limitations of inorganic materials in flexible and miniaturized applications, researchers have turned to composite structures using organic piezoelectric polymers as the matrix and doped with magnetic nanoparticles. This approach offers simple fabrication processes and strong mechanical adaptability, making it an important development direction for flexible magnetoelectric devices.

[0004] However, these particle composite structures are generally prepared using a blending and doping method, without active control over the spatial distribution of magnetic particles. The particles are prone to aggregation and gravitational sedimentation within the matrix, resulting in a disordered and non-uniform distribution that fails to form a continuous and ordered magneto-mechanical-electric coupling transmission pathway. Aggregated particles struggle to uniformly and efficiently transfer magnetostrictive stress to the piezoelectric phase, leading to significant stress dissipation and a low overall magneto-electric coupling coefficient. Consequently, the energy conversion efficiency and sensing sensitivity are insufficient to meet the practical application requirements of subcutaneous implantable devices for therapeutic power supply and diagnostic monitoring. Summary of the Invention

[0005] The purpose of this invention is to address the problems of random dispersion of magnetic nanoparticles, low interfacial coupling efficiency, and insufficient magnetic-electric energy conversion performance in existing magnetoelectric composite materials, and to provide a method for preparing flexible magnetoelectric composite films controlled by ultrasound / magnetic field. The method utilizes a direct curing process to prepare heterogeneous CFO / γ-Gly / PVA films. By introducing an ultrasonic field or bias magnetic field during the preparation process, flexible magnetoelectric composite films with different structures can be obtained, and the piezoelectric and magnetoelectric properties of the resulting films are improved.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] A method for preparing a flexible magnetoelectric composite thin film controlled by ultrasound / magnetic field includes the following steps:

[0008] Step S1: Mix 10wt% glycine (Gly) solution and 10wt% polyvinyl alcohol (PVA) solution at a volume ratio of 2:1, and stir until homogeneous to obtain a mixed solution;

[0009] Step S2: Cobalt ferrite (CFO) nanoparticles are doped into the mixed solution obtained in step S1 and dispersed by stirring to obtain a precursor solution;

[0010] Step S3: Dry the precursor solution obtained in step S2 at 60°C to form a film, so that glycine crystallizes into γ crystal form, and apply an ultrasonic field or a bias magnetic field to regulate the drying process.

[0011] Step S4: After the film dried in step S3 is naturally cooled to room temperature, it is peeled off to obtain a flexible magnetoelectric composite film.

[0012] Furthermore, the doping amount of the cobalt ferrite nanoparticles in step S2 is 2 wt% to 16 wt%.

[0013] Furthermore, the conditions for applying the ultrasonic field in step S3 are a frequency of 20kHz and a power of 120W, and the magnetoelectric composite thin film obtained by applying the ultrasonic field is of type 0-3.

[0014] Furthermore, the strength of the applied bias magnetic field is 60 mT, and the magnetoelectric composite thin film obtained when the bias magnetic field is applied is of type 2-2.

[0015] Furthermore, the mechanical stirring time in step S2 is 1 hour.

[0016] Furthermore, the average particle size of the cobalt ferrite nanoparticles described in step S2 is 40 nm.

[0017] Furthermore, the drying process in step S3 involves forming a film in a petri dish, and the amount of the precursor solution added is 0.2 to 0.4 mL per square centimeter of the bottom area of ​​the petri dish.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) Directional preparation of magnetoelectric thin films with different configurations: By introducing an ultrasonic field or a bias magnetic field, the spatial distribution of CFO nanoparticles in the thin film can be controlled in situ during the preparation process, and magnetoelectric composite thin films with two different configurations, namely 0-3 type and 2-2 type, are obtained respectively, thus realizing the controllable preparation of the microstructure of the thin film.

[0020] (2) Significantly improved piezoelectric properties: In this invention, glycine (Gly) and polyvinyl alcohol (PVA) are used as raw materials. During the film-forming process at 60 °C, hydrogen bonds are formed between the hydroxyl groups on the PVA molecular chain and the glycine molecules, inducing glycine to crystallize into a γ-crystalline form (γ-Gly) with a non-centrosymmetric structure, thus endowing the film with excellent piezoelectric properties. The doping of CFO nanoparticles further introduces local electric field, interfacial dipole coupling, and strain gradient effects, which significantly enhances the piezoelectric properties (see examples and details). Figure 7 ).

[0021] (3) Excellent magnetoelectric coupling effect: In this invention, CFO nanoparticles serve as a magnetostrictive phase. Their uniform dispersion (0-3 type) or layered enrichment distribution (2-2 type) can effectively transfer magnetostrictive stress, giving the film an excellent magnetoelectric coupling effect. Controlling the spatial distribution of CFO can enhance the magnetoelectric response, enabling the magnetostrictive stress generated by external magnetic field excitation to be uniformly and efficiently transferred to the surrounding piezoelectric matrix, significantly reducing stress transfer loss.

[0022] (4) Simple process and high repeatability: The preparation process of this invention only involves conventional operation steps such as solution mixing, doping dispersion, and drying to form a film. It is easy to operate, does not require complex equipment, has high repeatability, and is suitable for large-scale production.

[0023] (5) Excellent flexibility: The magnetoelectric composite film can withstand bending without breaking. It can be wound around the outside of the glass rod in a large curvature spiral shape while maintaining structural integrity. It has excellent flexibility and bendable deformation ability. It has good application prospects in the fields of battery-free implantable bioelectronic devices, magnetoelectric stimulation and physiological signal sensing, and can meet the application requirements of flexible electronic devices. Attached Figure Description

[0024] Figure 1 This is a schematic diagram of the CFO / γ-Gly / PVA thin film preparation process according to an example of the present invention;

[0025] Figure 2 Physical images and flexible illustrations of the γ-Gly / PVA and CFO / γ-Gly / PVA films prepared for embodiments of the present invention;

[0026] Figure 3 SEM images of γ-Gly / PVA and CFO / γ-Gly / PVA films prepared in embodiments of the present invention;

[0027] Figure 4 This is a material calculation structure diagram of an embodiment of the present invention;

[0028] Figure 5 Polarization diagrams of magnetoelectric thin films with different structures were calculated for the materials in the embodiments of the present invention;

[0029] Figure 6 The theoretical piezoelectric coefficients of different structured magnetoelectric thin films of the materials used in the embodiments of the present invention are calculated.

[0030] Figure 7 The piezoelectric properties of the CFO / γ-Gly / PVA thin film prepared in the embodiments of the present invention are shown in the figure.

[0031] Figure 8 The image shows the magnetoelectric properties of the CFO / γ-Gly / PVA thin film prepared according to an embodiment of the present invention. Detailed Implementation

[0032] The technical solution of the present invention will now be described in detail with reference to the accompanying drawings and embodiments.

[0033] like Figure 1 As shown, the method for preparing a flexible magnetoelectric composite thin film controlled by ultrasound / magnetic field in this embodiment includes the following steps:

[0034] Step S1, Raw material preparation:

[0035] Cobalt ferrite (CFO) nanoparticles, glycine (Gly), and polyvinyl alcohol (PVA) were all commercially available analytical grade reagents and were used directly.

[0036] Step S2, Preparation of mixed solution:

[0037] A 10wt% glycine solution and a 10wt% polyvinyl alcohol solution were mixed at a volume ratio of 2:1 and stirred until homogeneous to obtain a mixed solution.

[0038] Step S3, Preparation of precursor solution:

[0039] Cobalt ferrite nanoparticles were doped into the mixed solution obtained in step S2 and dispersed by stirring to obtain a precursor solution. The doping amount of the cobalt ferrite nanoparticles affects the ordered growth of the γ-induced crystal, while excessive doping inhibits crystallization. To ensure its functional feasibility, the doping amount of cobalt ferrite nanoparticles was determined to be 2 wt% to 16 wt%. In this embodiment, 0.16 g of cobalt ferrite nanoparticles were added to every 20 ml of mixed solution, and the solution was continuously stirred with a mechanical stirrer for 1 h to obtain a uniformly dispersed CFO precursor solution.

[0040] Step S4, Drying and Film Formation and Physical Field Control:

[0041] The precursor solution obtained in step S3 was slowly added dropwise to two plastic culture dishes, 2 mL of solution in each dish, until the solution completely covered the bottom surface of the culture dish. The culture dishes containing the precursor solution were placed in a 60°C forced-air oven for drying, and an ultrasonic field or bias magnetic field was applied to regulate the drying process.

[0042] The ultrasonic field was applied at a frequency of 20 kHz and a power of 120 W, and was continuously applied until the solution was completely dry to obtain a type 0-3 magnetoelectric composite film.

[0043] A bias magnetic field with an intensity of 60 mT was applied and continued until the solution was completely dry to obtain a type 2-2 magnetoelectric composite film.

[0044] Step S5, peeling

[0045] Remove the dried film from the culture dish along with the culture film from the fourth step and allow it to cool naturally to room temperature in air. Use tweezers to peel the crystalline film off the edge of the culture dish to obtain the flexible magnetoelectric composite film.

[0046] Comparative example: γ-Gly / PVA thin film

[0047] The method for preparing γ-Gly / PVA thin films in this comparative example is the same as that in Example 1. The only difference is that step S3 is not required in this comparative example. In this step, the mixed solution prepared in step S2 is directly added to the glass culture dish and dried, thus eliminating the need for the addition of CFO.

[0048] Figure 2 These are physical images and flexible illustrations of the thin films used in the embodiments. (a) is a γ-Gly / PVA thin film, (b) is a 0-3 type composite thin film, and (c) is a 2-2 type composite thin film. Figure 2 As can be seen, the γ-Gly / PVA film is translucent white; both composite films are black and exhibit surface uniformity, proving that the CFO nanoparticles are uniformly dispersed within them. Furthermore, (d) shows the magnetoelectric composite film bent into a semi-circular arc shape, demonstrating its ability to withstand bending without breaking, exhibiting a certain degree of flexibility. Further, Figure (e) shows the magnetoelectric film wrapped around the outside of a glass rod in a high-curvature spiral shape, demonstrating that the film maintains structural integrity even under more extreme curling deformation, visually proving its excellent flexibility and curling deformation capability.

[0049] Figure 3 SEM images of the γ-Gly / PVA and CFO / γ-Gly / PVA films prepared according to embodiments of the present invention are shown. From left to right, (I) is an optical image of the film cross-section, and (II) and (III) are elemental EDS images. Among them, (a) is an SEM image of the cross-section of the γ-Gly / PVA film according to an embodiment of the present invention. As can be seen from the optical image of the film cross-section, the γ-Gly / PVA film exhibits a layered structure. Characterization by elemental EDS images shows that the C element present in PVA and Gly is distributed in all regions of the film, while the N element present only in Gly is concentrated in the middle region of the film, indicating that the γ-Gly / PVA film exhibits a sandwich structure: Gly is enriched in the middle layer, and PVA is distributed at the top and bottom of the film.

[0050] Figure (b) shows a cross-sectional SEM image of the ultrasonically controlled 0-3 type CFO / γ-Gly / PVA thin film. The optical image of the film cross-section shows that the doping of CFO nanoparticles did not destroy the original sandwich structure of the γ-Gly / PVA film. Elemental EDS characterization shows that Fe elements present in CFO are distributed in all regions of the film, while N elements present only in Gly are concentrated in the central region of the film. This indicates that CFO nanoparticles are uniformly dispersed in the CFO / γ-Gly / PVA film prepared under ultrasonic control, forming a 0-3 type magnetoelectric composite structure.

[0051] Figure (c) shows a SEM cross-sectional image of the magnetically controlled 2-2 type CFO / γ-Gly / PVA thin film. The optical image of the film cross-section also shows that the doping of CFO nanoparticles did not disrupt the original sandwich structure of the γ-Gly / PVA film. Elemental EDS characterization reveals that Fe elements in the CFO nanoparticles are distributed on the top and bottom sides of the film, while N elements in the Gly are concentrated in the central region. This indicates that the magnetoelectric thin film prepared under magnetic field control forms a 2-2 type with a 5-layer structure. This successfully demonstrates that the structure of the CFO / γ-Gly / PVA thin film can be controlled by a physical field during its preparation.

[0052] Models were created for these three types of thin films; see the attached models. Figure 4 , Figure 4 In (a), γ-Gly / PVA is present. Figure 4 (b) represents type 0-3 CFO / γ-Gly / PVA. Figure 4 In the middle (c), it represents a 2-2 type CFO / γ-Gly / PVA. Based on... Figure 4 The established model calculates polarization values ​​to determine the effect of CFO nanoparticle doping on its piezoelectric properties, such as... Figure 5 As shown in (a), the undoped γ-Gly / PVA has the lowest polarization value of 0.652 C m. -2 ;like Figure 5 As shown in (b), the 0-3 type CFO / γ-Gly / PVA ratio is 0.703 cm. -2 ;like Figure 5 As shown in (c), the highest polarization value of the 2-2 type CFO / γ-Gly / PVA is 0.815 C m. -2 .

[0053] Six piezoelectric tensor components (d) of γ-Gly / PVA thin films, type 0-3 and type 2-2 composite structures. 11 d 14 d 15 d 22 d31 d 33 A comparison was performed. See the comparison results for details. Figure 6 Compared to the γ-Gly / PVA matrix, both doped CFO composite structures increased the absolute values ​​of each piezoelectric component. The longitudinal piezoelectric constant d of the 0-3 type composite structure was also improved. 33 The p-value is 10.08 pCN⁻¹, with the 2-2 type composite structure exhibiting the most significant reinforcing effect, and its longitudinal piezoelectric constant d0 is the highest. 33 The piezoelectricity can reach 12.55 pC N⁻¹. Calculations ultimately show that CFO doping did not reduce its piezoelectric properties; on the contrary, it enhanced its piezoelectric response. Specifically, the introduction of CFO doping significantly enhances the overall polarization. This is fundamentally due to the fact that CFO particles simultaneously introduce a local electric field, interfacial dipole coupling, and strain gradient effects. Furthermore, when CFO is uniformly distributed within the system, its local electric field and strain effects are spatially averaged, relatively weakening the polarization enhancement effect. However, when CFO is enriched in the upper and lower interface regions, the superposition effect of the built-in electric field and strain gradient is concentrated and oriented in the same direction, significantly enhancing both polarization and piezoelectric response.

[0054] The piezoelectric properties of γ-Gly / PVA thin films, 0-3 type and 2-2 type composite structures were measured, and the results are as follows: Figure 7 As shown, γ-Gly / PVA d 33 The lowest is 7.8 pC N. -1 ; Type 0-3 CFO / γ-Gly / PVA is 9.7 pC N -1 ; d of type 2-2 CFO / γ-Gly / PVA 33 The highest is 10.5 pC N -1 Consistent with the trend of theoretical calculations, the introduction of CFO nanoparticles has been proven, from theory to practice, to enhance the piezoelectric properties of the magnetoelectric thin film.

[0055] The magnetoelectric coefficients of γ-Gly / PVA thin films, 0-3 type and 2-2 type composite structures were measured, and the results are as follows: Figure 8 As shown, the magnetoelectric response of the undoped γ-Gly / PVA film is close to zero, while the magnetoelectric coefficient of the O-3 type magnetoelectric film tuned under an ultrasonic field is 6.1 mV cm⁻¹. -1 Oe -1 The magnetoelectric coefficient of the type 2-2 magnetoelectric thin film under magnetic field control is 16.4 mV / cm. -1 Oe -1 The results are all significantly higher than those of γ-Gly / PVA films. This demonstrates that controlling the spatial distribution of its CFO can enhance its magnetoelectric response, enabling the magnetostrictive stress generated by external magnetic field excitation to be uniformly and efficiently transferred to the surrounding piezoelectric matrix, with a significant reduction in stress transfer losses.

[0056] In summary, this invention provides a method for preparing flexible magnetoelectric composite films controlled by ultrasound / magnetic fields. By introducing different physical fields to precisely control the spatial arrangement and composite configuration of CFO nanoparticles, 0-3 and 2-2 type magnetoelectric composite structures were successfully constructed. These different structures can form more efficient and continuous magneto-mechanical-electric coupling transmission pathways, significantly improving the magnetoelectric coupling performance of the film, ultimately resulting in a high-performance CFO / γ-Gly / PVA film capable of multi-field driving. This film has good application potential in biomedical fields such as implantable bioelectronics and magnetoelectric diagnostic and therapeutic devices, and is suitable for preparing high-performance implantable physiological sensing and magnetoelectric stimulation devices. It can provide a high-quality material solution for the power supply and signal interaction modules of subcutaneous implantable diagnostic and therapeutic devices.

Claims

1. A method for preparing a flexible magnetoelectric composite thin film controlled by ultrasound / magnetic field, characterized in that, Includes the following steps: S1. Mix 10wt% glycine solution and 10wt% polyvinyl alcohol solution at a volume ratio of 2:1, and stir until homogeneous to obtain a mixed solution. S2. Cobalt ferrite nanoparticles are doped into the mixed solution obtained in step S1 and dispersed by stirring to obtain a precursor solution; S3. The precursor solution obtained in step S2 is dried at 60°C to form a film, and an ultrasonic field or a bias magnetic field is applied during the drying process for regulation. S4. After the film dried in step S3 is naturally cooled to room temperature, it is peeled off to obtain a flexible magnetoelectric composite film.

2. The method according to claim 1, characterized in that, The doping amount of the cobalt ferrite nanoparticles in step S2 is 2 wt% to 16 wt%.

3. The method according to claim 1, characterized in that, The conditions for applying the ultrasonic field in step S3 are a frequency of 20kHz and a power of 120W. Applying the ultrasonic field will produce a 0-3 type magnetoelectric composite thin film.

4. The method according to claim 1, characterized in that, The applied bias magnetic field strength is 60mT, and a 2-2 type magnetoelectric composite thin film is obtained when the bias magnetic field is applied.

5. The method according to any one of claims 1 to 4, characterized in that, The mechanical stirring time in step S2 is 1 hour.

6. The method according to any one of claims 1 to 4, characterized in that, The average particle size of the cobalt ferrite nanoparticles in step S2 is 40 nm.

7. The method according to any one of claims 1 to 4, characterized in that, The drying process in step S3 involves forming a film in a petri dish, and the amount of precursor solution added is 0.2 to 0.4 mL per square centimeter of the bottom area of ​​the petri dish.